2018
DOI: 10.1016/j.actbio.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing disulfiram for cancer therapy via targeted nanotechnology through enhanced tumor mass penetration and disassembly

Abstract: The β-d-galactose receptor targeted disulfiram loaded nanoparticle (LDNP) is novel in the following aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 36 publications
(40 reference statements)
3
36
0
Order By: Relevance
“…The nano-encapsulation protects the thiol groups in DS and extends its half-life in the serum from less than 2 min to over 7 h and successfully delivers the intact DS to cancer tissues [ 14 ]. In combination with oral administration of copper gluconate, the nano-encapsulated DS demonstrated significantly stronger anticancer efficacy in mouse breast, liver, ovarian, lung and brain cancer models [ 11 , 14 , 28 31 ] (and our unpublished data).
Fig.
…”
Section: Introductionmentioning
confidence: 66%
“…The nano-encapsulation protects the thiol groups in DS and extends its half-life in the serum from less than 2 min to over 7 h and successfully delivers the intact DS to cancer tissues [ 14 ]. In combination with oral administration of copper gluconate, the nano-encapsulated DS demonstrated significantly stronger anticancer efficacy in mouse breast, liver, ovarian, lung and brain cancer models [ 11 , 14 , 28 31 ] (and our unpublished data).
Fig.
…”
Section: Introductionmentioning
confidence: 66%
“…However, special interest has been paid to the publication about the manifestation of the anticancer properties of disulfiram . Subsequent studies on cancer cells and animal models have confirmed this observation …”
Section: An Aldehyde Dehydrogenase Inhibitor Disulfiram As An Anticanmentioning
confidence: 98%
“…[134,135] A combination of poly(pyridine-2-thiol) and copper could reverse the upregulation of oncogenes (CIRBP and STMN1) and the downregulation of tumor suppressor genes (CDKN1C and GADD45B) in tumor cells, which enhanced the specific cytotoxicity against cancer cells. Xu et al reported several GSH-responsive copper nanotoxins for specifically killing cancer cells.…”
Section: Copper Nanotoxinsmentioning
confidence: 99%
“…Xu et al reported several GSH-responsive copper nanotoxins for specifically killing cancer cells. [135] Adv. [134] They also synthesized poly(diethyldithiocarbamate) conjugated with β-D-galactose receptor targeting ligands.…”
Section: Copper Nanotoxinsmentioning
confidence: 99%